The law and practice of contractual receivership - Frisby, Sandra (2001)
The law of contractual receivership has evolved quietly over a period of one hundred and fifty years or so. The institution of receivership started out as a mortgagee's remedy, but has proved remarkably adaptable to the commercial needs of large financial organisations, so much so that it has enjoyed ascendancy as a method of debt enforcement for the latter half of the twentieth century. This thesis attempts to chart the developmental process of receivership law, and to evaluate both judicial and legislative responses to the particular issues of policy it raises. In particular, it investigates the impact of receivership, both in legal and practical terms, on the various parties interested, in their various capacities, in the corporate entity. The main body of the thesis addresses this question from a number of perspectives. Corporate insolvency affects a wide variety of constituents. Receivership, as an insolvency regime, is frequently criticised as overly biased in favour of powerful financial institutions at the expense of both the corporation itself and its other stakeholders. By affording a contractually appointed receiver dominion over the entirety of the company's property, and by sanctioning the proposition that his decisions be informed exclusively by his appointor's interests, this censure of the law might appear justified. Alternatively, proponents of receivership have promoted the institution as a 'rescue' mechanism, a means by which viable companies, or viable sectors of their businesses, may be nurtured back to productivity and profitability. These two conflicting views will be examined in the final Chapter, in the light of recent reform initiatives which appear to envisage at least some minor modification to the existing 'balance of power'.